PENARI PENCENG PADA PESTA GENDANG GURO-GURO ARON DALAM ACARA KERJA TAHUN DI DESA KETAREN KABUPATEN KARO: KAJIAN NILAI AN NORMA ADAT - Lilis Wuri Handayani Wuri Handayani (Universitas Negeri Medan, 2013)
Penceng dancers presented to tie enthusiasts visitors from outside the village in order to enliven the proceedings the time the dancers dance Penceng lot of motion that can invite negative thoughts in people who witnessed it.This study aimed to describe the existence of a corner dancers Penceng customary values ​​and norms prevailing in society Karo. To discuss the research objectives above ,use the theories related to the research topic,such as the sense of presence,understanding of customary norms and understanding of indigenous values​​. Time spent in research in discussing Penceng Dancers at the Guro - guro Aron Drum for 3 months.The place is the location of the study area Ketaren Village Kabanjahe Karo.Data analysis in this study uses descriptive kuliatatif ,techniques of data collection by,interviews ,documentation. Based on the research that has been done.In the whole dance Karo to move the legs,waist and around the eyes ,normally not allowed according to the norms of customs Karo.Penari Penceng originally presented to increase the number of existing aron nande the village now has the function of developing a broader ,binding enthusiasts to visitors from outside the village in order to enliven the proceedings.